2011
DOI: 10.1128/jcm.01732-10
|View full text |Cite
|
Sign up to set email alerts
|

The I222V Neuraminidase Mutation Has a Compensatory Role in Replication of an Oseltamivir-Resistant Influenza Virus A/H3N2 E119V Mutant

Abstract: Oseltamivir-resistant A/H3N2 influenza isolates with or without the E119V and I222V neuraminidase (NA) mutations were recovered from an immunocompromised patient. Based on plaque size, yield assays, and NA activity, the impaired viral fitness of the E119V mutant was partially restored by the I222V NA mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Moreover, our group has previously described the recovery of an oseltamivir-resistant influenza A/H3N2 virus harboring the I222V (I223V in N1 numbering) mutation in combination with E119V from an immunocompromised patient undergoing oseltamivir therapy (3). In these studies, the I223V substitution was found to alter the resistance phenotype, with a negative effect on replication kinetics of A/H5N1 viruses but improved viral fitness in the A/H3N2 subtype (3,16,32,36). The impact of amino acid changes at residue I223 has FIG 2 Seroconversion rates in ferrets infected with recombinant wild-type (WT), H275Y, and I223V-H275Y pH1N1 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our group has previously described the recovery of an oseltamivir-resistant influenza A/H3N2 virus harboring the I222V (I223V in N1 numbering) mutation in combination with E119V from an immunocompromised patient undergoing oseltamivir therapy (3). In these studies, the I223V substitution was found to alter the resistance phenotype, with a negative effect on replication kinetics of A/H5N1 viruses but improved viral fitness in the A/H3N2 subtype (3,16,32,36). The impact of amino acid changes at residue I223 has FIG 2 Seroconversion rates in ferrets infected with recombinant wild-type (WT), H275Y, and I223V-H275Y pH1N1 viruses.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the altered receptor-binding avidity and lower replication resulting from the antigenic escape mutation HA K165E in A/Puerto Rico/8/1934 (H1N1) could be compensated for by mutations in HA or the neuraminidase (NA) (15,16), and stabilizing mutations were required to occur prior to the introduction of immune-escape mutations in influenza A/H3N2 virus (17). Similarly, there are numerous examples where antiviral resistance-conferring mutations come at a fitness cost for the virus but can be compensated for by other mutations: several neuraminidase substitutions can occur and have occurred as either permissive or compensatory mutations to counteract the adverse fitness effects of the oseltamivir resistance mutation NA H275Y in influenza A/H1N1 virus (18)(19)(20), and similarly, the I222V NA mutation in influenza A/H3N2 virus partially restored the viral fitness-decreasing oseltamivir resistance mutation NA E119V (21).…”
mentioning
confidence: 99%
“…There are three complementary approaches to address these limitations: improving genetic prediction of biological traits, improving assays of these traits, and improving animal models of human transmission; all approaches are currently progressing in parallel (Holder et al, 2011; Simon et al, 2011). The first approach aims to further refine our understanding of sequence-to-trait relationships by continued studies of diverse, naturally or artificially produced mutations and their effects on the traits of interest.…”
Section: Discussionmentioning
confidence: 99%